1992
DOI: 10.1080/09064709209410131
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Study of Pubertal Age, Litter Traits, Weight Loss during Lactation and Relations to Growth and Leanness in Gilts

Abstract: S-755 97 Uppsala, Sweden. A genetic study of pubertal age, litter traits, weight loss during lactation and relations to growth and leanness in gilts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
21
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 23 publications
11
21
0
Order By: Relevance
“…The large phenotypic and genetic correlations between age and weight at puberty are in close agreement with most available literature estimates (Reutzel and Sumption, 1968;Young et al, 1978;Hutchens et al, 1981 (Reutzel and Sumption, 1968;Young et al, 1978, Hutchens et al, 1981, Rydhmer et al, 1992 …”
supporting
confidence: 90%
“…The large phenotypic and genetic correlations between age and weight at puberty are in close agreement with most available literature estimates (Reutzel and Sumption, 1968;Young et al, 1978;Hutchens et al, 1981 (Reutzel and Sumption, 1968;Young et al, 1978, Hutchens et al, 1981, Rydhmer et al, 1992 …”
supporting
confidence: 90%
“…Hanenberg et al (2001) and Holm et al (2004b). Results regarding the genetic correlation between growth and pubertal age by Rydhmer et al (1992) and those between growth and age at first farrowing by Rydhmer et al (1995) showed a high favorable genetic correlation (−0.31 and −0.61). A negative genetic correlation between ADG and AFC was also found in this study but it was close to zero.…”
Section: Genetic Parametersmentioning
confidence: 88%
“…Culling was also more frequent among the females owing to the design of the experiment, with farrowing in batches. The main reasons for culling females were, apart from illness, anoestrus and recycling after the first mating (Rydhmer et al, 1992).…”
Section: The Difference (66 G) In Generation Zero Is Used As a Measurmentioning
confidence: 99%